(untitled) - Lưu, Văn Lợi (Hà Nội, 2000)
Feudal Vietnam and the present Socialist Republic of Vietnam are fundamentally different with regard to their political regimes, but the Vietnamese state gas existed continuously activities over the years, but the foreign policies have much in common. The preservation of the national sovereignty and territory and the interests of the nation are like a red thread connecting the past and present.
Keywords: Diplomacy,International relations